High-Throughput Sequencing Facilitates Characterization of a “Forgotten” Plant Virus: The Case of a Henbane Mosaic Virus Infecting Tomato - Pecman, Anja; Kutnjak, Denis; Mehle, Nataša; Žnidarič, Magda Tušek; Gutiérrez-Aguirre, Ion; Pirnat, Patricija; Adams, Ian; Boonham, Neil; Ravnikar, Maja (Frontiers in Microbiology, 2018)
High-throughput sequencing has dramatically broadened the possibilities for plant virus research and diagnostics, enabling discovery of new or obscure viruses and virus strains and rapid sequencing of their genomes. In this research, we employed high-throughput sequencing to discover a new virus infecting tomato, Henbane mosaic virus (Potyvirus, Potyviridae), which was first discovered at the beginning of 20th century in the United Kingdom in cultivated henbane. A field tomato plant with severe necrotic symptoms of unknown aetiology was sampled in Slovenia and high-throughput sequencing analysis using small RNA and ribosomal RNA depleted total RNA approaches revealed a mixed infection with Potato virus M (Carlavirus, Betaflexiviridae), Southern tomato virus (Amalgavirus, Amalgamaviridae) and henbane mosaic virus in the sample. The complete genomic sequence of henbane mosaic virus was assembled from the sequencing reads. By re-inoculation of the infected material on selected test plants, henbane mosaic virus was isolated and a host range analysis was performed, demonstrating the virus was pathogenic on several plant species. Due to limited metadata in public repositories, the taxonomic identification of the virus isolate was initially putative. Thus, in the next step, we used small RNA sequencing to determine genomic sequences of four historic isolates of the virus, obtained from different virus collections. Phylogenetic analyses performed using this new sequence information enabled us to taxonomically position Henbane mosaic virus as a member of the Potyvirus genus within the chilli veinal mottle virus phylogenetic cluster and define the relationship of the new tomato isolate with the historic ones, indicating the existence of at least four putative strains of the virus. The first detection of henbane mosaic virus in tomato and demonstration of its pathogenicity on this host is important for plant protection and commercial tomato production. Since the virus was initially present in a mixed infection, and its whole genome was not sequenced, it has probably been overlooked in routine diagnostics. This study confirms the applicability of a combination of high-throughput sequencing and classic plant virus characterization methods for identification and phylogenetic classification of obscure viruses and historical viral isolates, for which no or limited genome sequence data is available.